Definisi Pembelajaran Kontekstual pada Pembelajaran IPA di Kelas IV SD Negeri Pengenrejo 2 - Dwi Nuril Hidayati; Gita Kumalasari; Atikah Riswandani (Indonesian Publication Center, 2023)
This research was conducted at SD Negeri Pangenrejo 2 with the aim of knowing whether the learning method using a contextual approach had been applied in the elementary school or not, especially in science learning and how the students responded when using a contextual approach learning method. The learning model with a contextual approach is a learning approach that can link learning materials with the problems faced by students in real life both in the family, school, or community environment. Learning methods using a contextual approach can make students more active because students have to find out information about learning materials independently. By using contextual learning, learning will be more meaningful and real, learning will be more fun and less boring, and learning will be more productive. The research method used in this study is a qualitative research method with data collection by observation, interviews, and teaching simulations in accordance with the lesson plans that have been made. The result of this research is that learning using contextual learning methods has not been fully implemented in every science lesson, because not all materials can be applied using contextual learning methods. The response of students when using contextual learning methods is that students do not feel bored when learning and better understand the learning material being taught and can relate it to problems that exist in everyday life.